2016
DOI: 10.1021/acs.nanolett.6b03218
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively in Situ Imaging Silver Nanowire Hollowing Kinetics

Abstract: We report the in situ investigation of the morphological evolution of silver nanowires to hollow silver oxide nanotubes using transmission X-ray microscopy (TXM). Complex silver diffusion kinetics and hollowing process via the Kirkendall effect have been captured in real time. Further quantitative X-ray absorption analysis reveals the difference between the longitudinal and radial diffusions. The diffusion coefficient of silver in its oxide nanoshell is, for the first time, calculated to be 1.2 × 10 cm/s from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 27 publications
5
39
1
Order By: Relevance
“…The hollowing process is driven by the nanoscale Kirkendall effect that originates from the outward diffusion of Ag atoms through the Ag 2 O layer to react oxygen, followed by thickening of the Ag 2 O layer. The typical snapshots of the in situ TXM study shown in Figure a highlight the corresponding geometrical evolution of the Ag nanowire during oxidation, which is similar to the typical hollowing process highlighted in Figure e . The intensity contrast in the TXM images originates from the spatially nonuniform distribution of Ag and Ag 2 O.…”
Section: In Situ X‐ray Characterizationsupporting
confidence: 54%
See 3 more Smart Citations
“…The hollowing process is driven by the nanoscale Kirkendall effect that originates from the outward diffusion of Ag atoms through the Ag 2 O layer to react oxygen, followed by thickening of the Ag 2 O layer. The typical snapshots of the in situ TXM study shown in Figure a highlight the corresponding geometrical evolution of the Ag nanowire during oxidation, which is similar to the typical hollowing process highlighted in Figure e . The intensity contrast in the TXM images originates from the spatially nonuniform distribution of Ag and Ag 2 O.…”
Section: In Situ X‐ray Characterizationsupporting
confidence: 54%
“…At t < 14 min, F(t) exhibits a good proportionality to G(t), providing the diffusion coefficient of Ag atoms in the thin Ag 2 O sheath being 1.2 × 10 −13 cm 2 s −1 . [130] The deviation from the proportionality at t > 14 min is ascribed to the complete separation of the Ag core and the Ag 2 O sheath, which significantly lowers the diffusion of Ag atoms into the Ag 2 O sheath. Instead, the surface-mediated diffusion mechanism shown in Figure 2 takes over to continuously consume the Ag core and grow the Ag 2 O shell.…”
Section: In Situ X-ray Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the detailed formation pathway of 1D nanowire and then guide the rational design of 1D nanowire, most observations and analyses have been carried out. In‐situ dark‐field optical microscopy has been used to reveal the rate‐limiting step during the nanowire formation, and in‐situ transmission X‐ray microscopy was used for relatively thick metal nanowires . In addition, electrochemical method was utilized to explore the actual role of capping agent during the formation of nanowire .…”
Section: One‐dimensional Nanowires Formationmentioning
confidence: 99%